Comparative Analysis on Structural Behaviour of Steel Structure Using Different Types of Bracing Due to Dynamic Earthquake Loads - Rosi Nursani; M Syarif Al Huseinny; Hidayanto Hidayanto (Universitas Negeri Yogyakarta, 2025)
Earthquake-resistant steel structures must have adequate strength and serviceability to withstand and distribute seismic forces throughout the structure. The structure should not be too stiff or too ductile. High structural stiffness causes small deformations in the structure and affects the absorption of seismic energy. On the other hand, structures that are too flexible can cause deformations beyond the structural limits. One effective approach to enhance earthquake resistance in high-rise buildings is the incorporation of lateral bracing. This study outlines a numerical simulation of a five-story steel building, employing various bracing types using specialized software. The objective is to assess the structural behavior of the building both with and without bracing, specifically analyzing three configurations: V-bracing, inverted V-bracing, and two-story X-bracing. Key aspects of the structural behavior examined include natural periods, internal forces, inter-story drift, and overall stiffness. All models maintain consistent dimensions for structural elements, loading conditions, and the placement of bracing, positioned in the building's weak direction. A dynamic analysis was conducted utilizing the response spectrum method. The findings reveal that structures equipped with inverted V-bracing and two-story X-bracing exhibit superior performance compared to those with V-bracing, while the V-bracing still offers enhancements over structures lacking any bracing.